Reflexões sobre o conceito de atendimento humanizado em Odontologia - Guerra, Camila Tuanny (2014)
Humanization at dental care is highly important due to uneven relation between scientific / technical advances in dentistry and thequality of human contact. The dental treatment goes beyond the field of scientific knowledge. Therefore, the dental treatment requiresbalance among technical skill, scientific training, and humanist vision of health promotion. Contemporarily, humanization is understoodas tripod based on user's rights, dental practice and organization of a humanized model. Curriculum integration of ethical, humanistic,scientific and technical contents is an important and current challenge on teaching / learning process for professionals at Dentistry. Thispaper aims to, guided by the literature review, to present some considerations on human care in dentistry, with emphasis on theimportance of professional /patient relationship for promoting oral health. It is suggested that dentists reflect on the urgent need ontheoretical basis of humanization and patient-professional relationship for health care.Descriptors: Humanization of Assistance; Dental Staff